Magnetic resonance imaging of a transient splenial lesion of the corpus callosum resolved within a week. Issue 1 (February 2016) - Conforti, R.; Porto, A.M.; Capasso, R.; Cirillo, M.; Fontanella, G.; Salzano, A.; Fabrazzo, M.; Cappabianca, S.
Abstract: The transient splenial lesion (TSL) of the corpus callosum (CC) is an uncommon radiologic finding incidentally detected on Magnetic Resonance Imaging (MRI). It was first observed in epileptic patients and ever since it has been described in varied neurologic conditions but its etiology is still little known. Slow disappearance of signal abnormalities in the CC mainly occurs after some weeks or months and then TSL carries a good prognosis making unnecessary invasive therapies and procedures. We report a case of an isolated TSL of CC in a patient suffering from psychotic and hormonal disorders, which spontaneously resolved within only one week. Highlights: Transient splenial lesion is an uncommon radiologic finding. It has been described in varied neurologic conditions. Slow disappearance of the lesion occurs after some weeks or months. Invasive diagnostic procedures or treatments may be avoided.